Multiple distinct pathways lead to hyperubiquitylated insoluble TDP-43 protein independent of its translocation into stress granules - Hans, Friederike (J Biol Chem, 2020)
Insoluble, hyperubiquitylated TAR DNA-binding protein of 43 kDa (TDP-43) in the central nervous system characterizes frontotemporal dementia and ALS in many individuals with these neurodegenerative diseases. The causes for neuropathological TDP-43 aggregation are unknown, but it has been suggested that stress granule (SG) formation is important in this process. Indeed, in human embryonic kidney HEK293E cells, various SG-forming conditions induced very strong TDP-43 ubiquitylation, insolubility, and reduced splicing activity. Osmotic stress–induced SG formation and TDP-43 ubiquitylation occurred rapidly and coincided with colocalization of TDP-43 and SG markers. Washout experiments confirmed the rapid dissolution of SGs, accompanied by normalization of TDP-43 ubiquitylation and solubility. Surprisingly, interference with the SG process using a protein kinase R–like endoplasmic reticulum kinase inhibitor (GSK2606414) or the translation blocker emetine did not prevent TDP-43 ubiquitylation and insolubility. Thus, parallel pathways may lead to pathological TDP-43 modifications independent of SG formation. Using a panel of kinase inhibitors targeting signaling pathways of the osmotic shock inducer sorbitol, we could largely rule out the stress-activated and extracellular signal–regulated protein kinase modules and glycogen synthase kinase 3β. For arsenite, but not for sorbitol, quenching oxidative stress with N-acetylcysteine did suppress both SG formation and TDP-43 ubiquitylation and insolubility. Thus, sodium arsenite appears to promote SG formation and TDP-43 modifications via oxidative stress, but sorbitol stimulates TDP-43 ubiquitylation and insolubility via a novel pathway(s) independent of SG formation. In conclusion, pathological TDP-43 modifications can be mediated via multiple distinct pathways for which SGs are not essential.